1967
DOI: 10.1055/s-0038-1654100
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hirudin, a Potent Antithrombin, on the Thromboplastin Generation Test

Abstract: SummaryThe presence of hirudin at the time adsorbed plasma and serum were combined in TGT inhibited the formation of the prothrombin converting activity. Hirudin, a potent antithrombin, probably exerted its inhibitory effect by neutralizing any thrombin which might form. If adsorbed plasma and serum were incubated together for a period as short as 1 to 3 min before the addition of hirudin, calcium and lipid, hirudin no longer exerted the same inhibitory effect, but, in order to exert the same inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[14][15][16][17]33,35,[37][38][39] During the period 1955 to 1960, several groups of investigators found hirudin to be a specific inhibitor of thrombin. 40,41 Because of its remarkable specificity to thrombin, hirudin was used as a reagent in biochemical studies on the action of thrombin. Despite the high cost and labor associated with isolation and purification procedures, Markwardt and coworkers performed most of the basic biochemical and pharmacologic studies on natural hirudin.…”
Section: Overviewmentioning
confidence: 99%
“…[14][15][16][17]33,35,[37][38][39] During the period 1955 to 1960, several groups of investigators found hirudin to be a specific inhibitor of thrombin. 40,41 Because of its remarkable specificity to thrombin, hirudin was used as a reagent in biochemical studies on the action of thrombin. Despite the high cost and labor associated with isolation and purification procedures, Markwardt and coworkers performed most of the basic biochemical and pharmacologic studies on natural hirudin.…”
Section: Overviewmentioning
confidence: 99%